Le projet comme dynamique de l’élaboration d’une compétence collective chez une équipe d’enseignants du premier degré - Sylviane Blanc-Maximin; Chantal Eymard (Éducation et Socialisation)
This article discusses the development of a collective competency within a team of primary school teachers. Research into the benefits of pooling skills is available in the corporate world, but still fairly uncommon in the teaching one. Our aim is to find whether the avowed or confirmed presence of collective projects in the school is linked with the existence of observable change indicators, in terms of school effectiveness. On one hand, an enquiry was realized with two hundred rural and urban-based school teams, with a variable number of classes. Information about teamwork, related to a collective project, is gathered. On the other hand, logbooks are drafted by newly appointed teachers. They tell about their working walkthroughs situations, during which the teaching team mobilizes a possible competence of collective nature.